The Relationship Between the Modified Glasgow Prognostic and SYNTAX Scores in Patients with Non-ST Elevation Myocardial Infarction - Ahmet KARADUMAN; Cemalettin YILMAZ; Mustafa Ferhat KETEN; Ismail BALABAN; Zeynep Esra GUNER; Mehmet CELIK (Medeniyet Medical Journal)
Objective: This study investigated the modified Glasgow prognostic score (mGPS) to determine its predictive value and how it could be compared with various inflammatory markers, including C-reactive protein (CRP) to albumin ratio and neutrophil-to-lymphocyte ratio, for determining the extent and severity of coronary artery disease (CAD) in patients with non-ST-elevated myocardial infarction (NSTEMI). Methods: This study analyzed the cases of 295 patients with NSTEMI who had undergone coronary angiography. In an effort to determine the seriousness and scope of CAD in each patient, the Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX) score was calculated and then assessed. The study sample was divided into two separate groups based on the SYNTAX score: moderate to high SYNTAX (>22) and low SYNTAX (≤22). Results: There were 295 patients (23.1% female, 76.9% male) included in the research, with an average age being 61.2+-10.9 years, and the mean SYNTAX score being 7.3+-10.4 (range: 0-40). Those with a SYNTAX score >22 were observed to possess significantly higher levels of CRP, CRP/albumin ratio, and mean mGPS 1-2 ratios compared with those with a SYNTAX score ≤22 (all p<0.001). Smoking [odds ratio (OR): 3.341, 95% confidence interval (CI): 1.531-7.294; p=0.002], CRP/albumin ratio (OR: 4.958, 95% CI: 1.335-18.418; p=0.017), and mGPS score of 1-2 (OR: 3.121, 95% CI: 1.430-6.814; p=0.004) were independent factors used to help predict a high SYNTAX score. Conclusions: It seems possible to make use of the mGPS when estimating the degree and intricacies of CAD in patients with NSTEMI, as there appears to be a connection with higher SYNTAX scores.